The challenge of using patient reported outcome measures in clinical practice: how do we get there? - David Cella; Kyle Nolla; John Devin Peipert (Journal of Patient-Reported Outcomes, 2024)
Abstract Background As patient-reported outcome measures (PROMs) become available to clinicians for routine clinical decision-making, many wonder how to define a meaningful change in a patient’s PROM score. Some PROMs have a specific threshold that indicates meaningful change, but since those numbers are based on population averages, they do not necessarily apply to the varying experiences of each individual patient. Rather than viewing this as a weakness of PROMs, it is worth considering how clinicians use other existing measures in clinical decision-making—and whether PROMs can be used similarly. Body An informal survey of 43 clinicians reported using measures such as weight, blood pressure, and blood chemistry to inform clinical decision-making. Although clinicians were very consistent with what constituted a meaningful change for some measures (e.g., ECOG performance status), other measures had considerable variability (e.g., weight), often informed by their specialization (for example, differing thresholds for meaningful weight change for adult primary care, pediatrics, and oncology). For interpreting change in measures, they relied on clinical experience (44%), published literature (38%), and established guidelines (35%). In open-response comments, many clarified that the results of any measure had to be taken in the context of each individual patient before making treatment decisions. In short, clinicians already apply individualized clinical judgment when interpreting score changes in existing clinical measures. As clinicians gain familiarity with PROMs, PROMs will likely be utilized in the same way. Conclusion Like other clinical measures from weight to blood chemistry, change in a PROM score is but one piece of a patient’s clinical story. Rather than relying on a hard-and-fast number for defining clinically meaningful change in a PROM score, providers should—and many already do—consider the full scope of a patient’s experience as they make treatment decisions.